Frequency of Cesarean Section in Premature Rupture of Membranes - Shahida Magsi, Sonia Gul Qureshi, Fatima Rajput, Basma Zia, Inayatullah Magsi (Pakistan Journal of Medical & Health Sciences, 2022)
Background: Premature rupture of membranes (PROM) is always of clinical significance either it occurs before onset of labour at term or preterm. It is defined as spontaneous rupture of fetal membranes which results in leakage of amniotic fluid. PROM is related with maternal and perinatal morbidity and mortality if not treated sensibly on time, due not only to conditions causing it but also likelihood of emergency cesarean delivery. Aim: To ascertain frequency of C- section in women presented with premature rupture of membranes at tertiary care hospital. Study Design: Cross-sectional descriptive study Place and Duration of Study: Department of Obstetrics and Gynaecology Unit 1, Sheikh Zayed Women Hospital, Shaheed Mohtarma Benazir Bhutto Medical University Larkana from 1st October 2020 to 30th April 2021 Methodology: One hundred and eighty six pregnant women having gestation from 28 weeks till 40 weeks and diagnosed as premature rupture of membranes were included. Results: The average age 27.97±5.66 years. 29.57% of caesarean section presented PROM was observed. Conclusion: PROM remains an imperative cause of maternal and fetal morbidity and increased rate of cesarean section delivery to focus upon. Timely evaluation of reasons leading to PROM can help us in reducing the soaring rate of cesarean section in developing countries. Keywords: Premature rupture of membranes, Caesarean section, complications.